Strategies for mitigating N2O and N2 emissions from an intensive sugarcane cropping system - Johannes Friedl; Daniel Warner; Weijin Wang; David W. Rowlings; Peter R. Grace; Clemens Scheer (Nutrient Cycling in Agroecosystems, 2023)
In sugarcane cropping systems, high rates of N fertiliser are typically applied as sub-surface bands creating localised zones of high mineral N concentrations. This in combination with high levels of crop residue (trash) retention and a warm and humid climate creates conditions that are known to promote soil denitrification, resulting in high emissions of the potent greenhouse gas N 2 O. These losses illustrate inefficient use of N fertilisers but total denitrification losses in the form of N 2 and N 2 O remain largely unknown. We used the 15 N gas flux method to investigate the effect of cane trash removal and the use of the nitrification inhibitor 3,4-dimethylpyrazole phosphate (DMPP) on N 2 and N 2 O emissions on a commercial sugarcane farm at Bundaberg, Australia. High gaseous N losses were observed under the standard grower practice where cane trash retention and N fertiliser application (145 kg N ha −1 as urea) resulted in N 2 and N 2 O emissions (36.1 kg N ha −1 ) from the subsurface N fertiliser band, with more than 50% of these losses emitted as N 2 O. Cane trash removal reduced N 2 emission by 34% and N 2 O emission by 51%, but had no effect on the N 2 O/(N 2 + N 2 O) ratio. The use of DMPP lowered N 2 and N 2 O emission by 35% and 98%, respectively, reducing the percentage of these losses (N 2 + N 2 O) emitted as N 2 O to only 4%. We conclude that the use of DMPP is an effective strategy to reduce N losses, minimise N 2 O emissions, while keeping the benefits of cane trash retention in sugarcane cropping systems.

The bacterium Pseudomonas protegens antagonizes the microalga Chlamydomonas reinhardtii using a blend of toxins - Magdalena M. Rose; Daniel Scheer; Yu Hou; Vivien S. Hotter; Anna J. Komor; Prasad Aiyar; Kirstin Scherlach; Fredd Vergara; Qing Yan; Joyce E. Loper; Torsten Jakob; Nicole M. van Dam; et al. (Environmental Microbiology, 2021)
Summary The unicellular alga Chlamydomonas reinhardtii and the bacterium Pseudomonas protegens serve as a model to study the interactions between photosynthetic and heterotrophic microorganisms. P . protegens secretes the cyclic lipopeptide orfamide A that interferes with cytosolic Ca 2+ homeostasis in C . reinhardtii resulting in deflagellation of the algal cells. Here, we studied the roles of additional secondary metabolites secreted by P . protegens using individual compounds and co‐cultivation of algae with bacterial mutants. Rhizoxin S2, pyrrolnitrin, pyoluteorin, 2,4‐diacetylphloroglucinol (DAPG) and orfamide A all induce changes in cell morphology and inhibit the growth of C . reinhardtii . Rhizoxin S2 exerts the strongest growth inhibition, and its action depends on the spatial structure of the environment (agar versus liquid culture). Algal motility is unaffected by rhizoxin S2 and is most potently inhibited by orfamide A (IC 50 = 4.1 μM). Pyrrolnitrin and pyoluteorin both interfere with algal cytosolic Ca 2+ homeostasis and motility whereas high concentrations of DAPG immobilize C . reinhardtii without deflagellation or disturbance of Ca 2+ homeostasis. Co‐cultivation with a regulatory mutant of bacterial secondary metabolism (Δ gacA ) promotes algal growth under spatially structured conditions. Our results reveal how a single soil bacterium uses an arsenal of secreted antialgal compounds with complementary and partially overlapping activities.